EncontrAR: Informe Situacional de la Plataforma de Aprendizaje Colaborativo - Mercado, P.; Angulo, L.; Haan, Stef de; Ochoa, J.; Castellanos, A.; Pradel, W. (International Potato Center, 2023)
One of the options for the development of family farming is to promote access to different markets (national or international). Related to this, various contributions in relation to the analysis of the development problems of rural markets highlight two fundamental aspects that must be faced: the few opportunities in local markets and the limited access to more dynamic markets with competitive products. The dynamism of the markets constitutes the main axis of economic development. Accessing the market and its benefits depends on the competitive capacity of individuals and their environments (territories). Competitive capacity is manifested in the ability to meet the demands of the markets. The latter refer, for example, to the norms and standards of quality, homogeneity, consistency, volume, continuity (in supply), health, safety, guarantees of quality and origin (certifications, seals, designations of origin) and compliance with commitments. In the high Andes, the elements to make this process of promoting viable markets are based on: i) the construction of networks and alliances: the sustainability of an intervention model is based on the construction of networks and alliances involved in development at different levels; ii) programmatic articulation: between the various components and objectives, it constitutes a condition for the sustainability of the processes and results (this has its expression at the level of the same population in which multisectoral interventions converge); iii) territorial development: the intervention is planned on the basis of the territory, understood as the organized, complex and living set of economic, social and cultural relations of civil society and the State. Special attention should be paid to promoting the participation of women in different activities. One of the objectives of Perumin Inspira is aimed at strengthening capabilities. Entrepreneurs value strengthening their capabilities to better take advantage of all these business opportunities. A second point has to do with taking as a basis the development of innovations that generate value in products. A third point comes from the fact that the ventures seek to promote development at the local and regional level. They are ventures that are in the same areas that can interact in different contexts and demonstrate that if it is possible to promote businesses at a local and regional level, they take advantage of opportunities and generate a kind of ecosystem that allows interaction with different public and private actors in vulnerable areas such as high Andes.